Impact of AI-Powered ChatBots on EFL Students' Writing Skills, Self-Efficacy, and Self-Regulation: A Mixed-Methods Study - Apriani, Eka; Cardoso, Luis; Obaid, Ahmed J.; Wijayanti, Erfin; Esmianti, Farida; Supardan, Dadan; Muthmainnah, Muthmainnah (Global Educational Research Review, 2024)
Purpose – The study explores the impact of AI-powered ChatBots on English as a Foreign Language (EFL) students' writing skills, self-efficacy, and self-regulation. Given the rapid integration of digital tools in education, particularly in language learning, the research aims to fill a gap in understanding how ChatBot technology can enhance writing abilities, address psychosocial factors, and support self-regulated learning among EFL students. Design/Methods/Approach – A sequential explanatory mixed-methods approach was employed, involving 40 EFL students from IAIN Curup. Participants were divided into a control group (traditional writing instruction) and an experimental group (ChatBot-assisted instruction). Quantitative data on writing proficiency, self-efficacy, and self-regulation were collected through pre- and post-tests, followed by qualitative insights gathered through semi-structured interviews with the experimental group. Statistical analysis, including paired t-tests and ANCOVA, was used to assess differences between groups. Findings – The results revealed that students using ChatBots showed significant improvements in writing proficiency (post-test scores increased from 55.84 to 88.92), self-efficacy (from 20.46 to 30.38), and self-regulation (from 14.51 to 19.65). Interviews highlighted increased confidence, motivation, and engagement among students, though concerns about over-reliance on ChatBots and the risk of plagiarism were noted. Originality/Value – This research offers new insights into the use of AI-powered ChatBots in enhancing EFL students' writing skills, self-efficacy, and self-regulation. It addresses gaps in the literature by focusing on the psychosocial factors influencing writing performance and the potential benefits and drawbacks of AI integration in education. Practical Implications – The findings suggest that educators can use ChatBots to improve writing instruction, fostering autonomy and providing immediate feedback. However, strategies must be developed to avoid over-reliance on AI tools, ensuring students maintain creativity and critical thinking. Keywords AI-powered ChatBots, EFL writing, self-efficacy, self-regulation, language learning. Paper type Research paper